Pemanfaatan Media Microsoft Powerpoint Yang Menjadi Penunjang Dalam Bidang Pendidikan dan Perusahaan - Nurul Haliza; Vani Hajari; Ulfah Amirah Khairi; Mhd Dimas Jayadi; Nurbaiti Nurbaiti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This research was conducted based on the collection of information about the use of Microsoft PowerPoint which is a supporter in the field of education and companies. Microsoft PowerPoint is a media application / software that is made as a tool to support the running of the presentation. Microsoft PowerPoint was also developed by an application program called Microsoft Office which also includes Microsoft Word, Excel, and several other programs. From the results of the study it can be concluded that the use of Microsoft PowerPoint in the field of education for teachers, lecturers, and students is very helpful, because Microsoft PowerPoint only contains important points and has an attractive appearance such as being able to add slide layout features, object animations, text effects, images, videos, or audio so that the audience becomes interested in listening and does not feel bored. Meanwhile, the use of Microsoft PowerPoint in the corporate sector is to present business strategies, problem solving methods, explain financial reports, related to product sales and purchases, as well as reports on the latest company conditions.